2020
DOI: 10.21203/rs.3.rs-25210/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic insights into the diversity of carbohydrate-degrading enzymes in the yak fecal microbial community

Abstract: Background: As a special herbivorous ruminant, yak is supposed to utilize the gastrointestinal microbiota to digest plant materials. Although the cellulolytic bacteria of yak rumen have been reported, there is still limited information about whether carbohydrate metabolizing enzymes in its intestinal flora are abundant for the degradation of complex lignocellulosic biomass. Results: Here, this study aimed to decode the structure and function of yak fecal microbiota using deep metagenome sequencing. A compreh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Meanwhile, these microbial taxa play an important role in the utilization rate of assimilated nutrients (Krajmalnik-Brown et al 2012;Tett et al 2021), and could help hosts obtain energy from the relatively harsh environments of winter. In contrast to the gut microbiota of other plateau mammals such as the Tibetan wild ass (Equus kiang) (Gao et al 2020) and yak (Gong et al 2020), the abundance of Verrucomicrobiota in the intestines of the plateau pikas was very high, and had the highest relative abundance in summer. Akkermansia, the dominant resident genus of phylum Verrucomicrobiota, is well characterized to be an obligate host mucin degrader and usually be promoted by plant secondary compounds in food (Zhang et al 2018b;Dong et al 2021;Ren et al 2021)-for example, berberine promoted Akkermansia growth via stimulating mucin secretion in colon of mice (Dong et al 2021).…”
Section: Changes In Gut Microbial Compositionmentioning
confidence: 65%
See 1 more Smart Citation
“…Meanwhile, these microbial taxa play an important role in the utilization rate of assimilated nutrients (Krajmalnik-Brown et al 2012;Tett et al 2021), and could help hosts obtain energy from the relatively harsh environments of winter. In contrast to the gut microbiota of other plateau mammals such as the Tibetan wild ass (Equus kiang) (Gao et al 2020) and yak (Gong et al 2020), the abundance of Verrucomicrobiota in the intestines of the plateau pikas was very high, and had the highest relative abundance in summer. Akkermansia, the dominant resident genus of phylum Verrucomicrobiota, is well characterized to be an obligate host mucin degrader and usually be promoted by plant secondary compounds in food (Zhang et al 2018b;Dong et al 2021;Ren et al 2021)-for example, berberine promoted Akkermansia growth via stimulating mucin secretion in colon of mice (Dong et al 2021).…”
Section: Changes In Gut Microbial Compositionmentioning
confidence: 65%
“…2020) and yak (Gong et al . 2020), the abundance of Verrucomicrobiota in the intestines of the plateau pikas was very high, and had the highest relative abundance in summer. Akkermansia , the dominant resident genus of phylum Verrucomicrobiota, is well characterized to be an obligate host mucin degrader and usually be promoted by plant secondary compounds in food (Zhang et al .…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, the hindgut-enriched SGBs belonging to Alistipes spp. lacked dockerin modules, and the Kiritimatiellae-affiliated SGBs that were enriched in the small intestine encoded myriad GH109 enzymes to degrade glycans derived from host mucins [18] (Additional file 1: Table S10). These results indicate that microbes placed in the four-chambered stomach provide efficient hydrolysis for complex glycan breakdown to deal with primary dietary substrates.…”
Section: Genome-based Characterization Of Glycan-degrading Microbes A...mentioning
confidence: 99%
“…Other than these cellulolytic bacteria in the rumen, the diversity of the prevalent rumen microorganisms and putative carbohydrate-active enzymes for utilization of lignocellulosic biomass are also important in host adaptation of high plateau ( Bohra et al, 2019 ). Gong et al (2020) suggested complex gene repertoire composed of diverse carbohydrate-degrading enzymes for yak gut microbiota which provide multiple catalytic abilities of various carbohydrate substrates deconstruction. Zhao et al (2022) also reported a larger gene pool encoding rich in carbohydrate-active enzymes in the yak rumen microbiota by metagenomic analysis.…”
Section: Overview Of Rumen/gut Microbiota In Wild and Domesticated In...mentioning
confidence: 99%